Ayurpharmacoepidemiology Perspective - Parikshit Debnath MD (Ayurveda); Khurshid Natasha MPH, PhD; Liaquat Ali MPhil, PhD; Tapas Bhaduri MD (Ayurveda); Tushar Kanti Roy MD (Ayurveda); Sayantan Bera MD (Ayurveda); Debdeep Mukherjee MPH; Swati Debnath BAMS (SAGE Publishing, 2017)
Older Indian diabetics lack proper health literacy making them vulnerable to complications. Assessment of health literacy was done by hospital-based cross-sectional study. Face-to-face interview was conducted by pretested structured questionnaires. Diabetes patients aged ≥60 years consisted of 56.22% males and 43.78% females; in addition, 34.2% respondents were without formal schooling. Diabetes was known to 63.56% respondents. Total knowledge and practice score of the respondents was good (18.9% and 35.1%), average (30.7% and 46.9%), and poor (50.4% and 18%), respectively. Knowledge and practice score was strongly associated ( P < .01) with religion, educational status, and diabetes duration with positive relationship ( R 2 = 0.247, P < .01) between knowledge and practice score. The study highlights lack of health literacy among older diabetics undergoing ayurveda management. Baseline statistics will pave the way toward ayurpharmacoepidemiology.